Resilient rainfed technologies for drought mitigation and sustainable food security - RAO, CH. SRINIVASA; GOPINATH, K. A. (MAUSAM, 2016)
Even though drought is one of the most common features affecting rainfed agriculture, it is necessary to consider it as an extreme climatological event that requires different types of alleviating strategies for overcoming it. The risk involved in successful cultivation of crops depends on the nature of drought (chronic and contingent), its probable duration, and frequency of occurrence within the season. These aberrations are expected to further increase in future. A significant fall in food production is often noticed with increase in intensity or extension in duration of drought prevalence. Drought affects not only the food production at farm level but also the national economy and overall food security. Location-specific rainfed technologies are available to cope with different drought situations. Much of the research done in rainfed agriculture in India relates to conservation of soil & rainwater and to drought proofing. The key technologies for drought mitigation are in situ moisture conservation, rainwater harvesting and recycling, resilient crops and cropping systems including contingency crop plans, foliar sprays, and integrated farming systems. However, drought preparedness and real time implementation of contingency measures at field level needs well structured institutional support for farmers with strong government policy and convergence among various institutions. Ministry of Agriculture, Government of India, needs to facilitate the convergence process of various government schemes such as MGNREGA, RKVY, Mega Seed Project, NFSM, NHM, IWMP, Soil health schemes etc. for drought preparedness. National Mission for Sustainable Agriculture (NMSA), one among the missions under the Prime Minister National Action Plan for Climate Change (NAPCC) may take a lead role in implementation of contingency, by inclusion of this activity in State Action Plans (SAP) with a dedicated Nodal Institution /officers and budget provision.